Effect of grain boundaries on charge transport in CVD-grown bilayer graphene. (June 2019) - Wu, Jun; Li, Yongchao; Pan, Danfeng; Jiang, Chenghuan; Jin, Chen; Song, Fengqi; Wang, Guanghou; Wan, Jianguo
Abstract: Grain boundaries (GBs) in polycrystalline graphene could significantly modulate the physicochemical properties of graphene films, and have attracted intense interest. However, fundamental magnetotransport mechanisms of GBs in bilayer graphene grown by chemical vapour deposition (CVD) are scarcely reported. In this work, we synthesize bilayer graphene bicrystals on polycrystalline Cu foils and measure the electronic properties of such grains as well as of individual graphene grain boundaries. Interestingly, the pronounced metallic character of GB is observed, which is dramatically different from individual grains. Large linear magnetoresistance in graphene bicrystals is observed, which attributes to inhomogeneous charge transport, decorated by quantum interference effects at low temperatures. The measurement data show that individual boundaries between coalesced grains impede electrical transport, suppress the magnetoresistance and enhance intervalley scattering, leading to degradation of electrical performance of CVD graphene. Nevertheless, GBs embedded in a perfect graphene sheet can tune its electronic structure at the nanoscale, act as quasi-one-dimensional metallic wires and can be used as good candidates for strong magnetic field sensors. This work is beneficial to the fundamental understanding of the role of GBs in CVD-grown graphene and opens a potential avenue of application for polycrystalline bilayer graphene in functional devices. Graphical abstract: The pronounced metallic character of grain boundary is observed in bilayer graphene bicrystals synthesized using the solid-state-source CVD method, which is dramatically different from individual grains. Electrical transport measurements show that individual boundaries between coalesced grains impede electrical transport, suppress the magnetoresistance and enhance intervalley scattering in graphene. Image 1